The Public Participation in the Drafting of Legislation in Hungary - László Vértesy (Central European Public Administration Review)
The legitimacy of legislation is crucial for modern democracies. This paper provides a brief but detailed description and legal, quantitative analysis of this process, drawing attention to the most significant Hungarian techniques. According to the main provisions of Act CXXXI of 2010 on public participation in the drafting of legislation, public consultations are to be carried out within the framework of general or direct consultations. The general consultation is mandatory and open for the public, all draft bills, governmental decrees and ministerial decrees drafted by ministries are to be published on the Government’s webpage. The direct consultation is based on strategic partnerships between the relevant ministries and stakeholders, outstanding organisations. In Hungary, it is the responsibility of the minister competent to draft the legislation to open and conduct public consultation and to process the received comments. These mandatory and optional processes strengthen the legitimacy and the acceptance of legislation. As a consequence of this the legal provisions meet with the social requirements, and they can be applied as a best practice for other countries.